Beech forest structure and territory size of four songbird species in Puszcza Bukowa, NW Poland: implications for bird-friendly silvicultural practices in a temperate forest. Issue 2 (4th March 2018) - Skorupski, Jakub; Jankowiak, Łukasz; Kiriaka, Beata; Rek, Tomasz; Wysocki, Dariusz
Abstract : Despite the fact that the structure of a forest, its vegetation composition and the species diversity in its tree stands are among the key factors shaping avian communities in forests in general, there are few studies on this topic relating to the deciduous forests of Central and East-Central Europe. The aim of the present study was therefore to investigate the relationship between the forest structure and the occurrence of common chaffinch Fringilla coelebs, wood warbler Phylloscopus sibilatrix, common chiffchaff Phylloscopus collybita and Eurasian blackcap Sylvia atricapilla, and also investigate habitat occupancy as expressed by territory size, in certain areas of NW Poland. The hypothesis tested was that if a habitat is rich, then the territory should be smaller. The mean territory size was 0.704 ha in the case of F. coelebs, 0.307 ha for P. sibilatrix, 0.148 ha for P. collybita and 0.312 ha for S. atricapilla . The use of a generalised linear mixed model demonstrated statistically significant relationships between the environmental variables and the territory size of the target bird species, the number of trees being the most significant environmental variable positively correlated with the territory size of birds. With regard to the canopy, a statistically significant negative relationship was demonstrated between the environmental variables and the territory size, whereas in the case of shrubs it was positive. The obtained results indicate need to restore the diversified structure of beech forests by ensuring the heterogeneity of forest stands, to increase avian diversity in managed forests.